Graves' disease: a review of surgical indications, management, and complications in a cohort of 59 patients. Issue 6 (June 2015) - Stathopoulos, P.; Gangidi, S.; Kotrotsos, G.; Cunliffe, D.
Abstract An analysis of 59 patients who underwent total thyroidectomy for the treatment of Graves' disease over a 6-year period was conducted in order to assess the current indications and identify any specific factors that may influence the patient's decision to opt for surgical treatment. A comparison of outcomes between the current study and a similar one from Hong Kong was also attempted. Patient preference was the most common reason for opting for surgery over radioactive iodine in both studies. Other indications for surgery, such as Graves' ophthalmopathy, patient refusal for radioactive iodine, large goitre with pressure symptoms, planning for pregnancy, young age, and intolerance to anti-thyroid drugs, were also similar in the two groups. There were no statistically significant differences in laryngeal nerve palsy between the two groups. The rates of permanent hypoparathyroidism in patients in Hong Kong and in the present study were 5.4% and 5.1%, respectively. No patient in either study had recurrent Graves' disease after total thyroidectomy. Our findings confirmed that patient preference is the leading indication for surgery, implicating a continuous misconception of radioactive substances and increasing confidence in surgical outcomes. In experienced hands, the risks of recurrent laryngeal nerve injury and permanent hypoparathyroidism remain minimal.